Transforming the construction sector: an institutional complexity perspective. Issue 2 (14th August 2021) - Oti-Sarpong, Kwadwo; Pärn, Erika Anneli; Burgess, Gemma; Zaki, Mohamed
Abstract : Purpose: Government initiatives to improve construction have increasingly become more focused on introducing a repertoire of technologies to transform the sector. In the literature on construction industry transformation through policy-backed initiatives, how firms will respond to the demands to adopt and use innovative technologies and approaches is taken for granted, and there is scarcely any attention given to the institutional implications of transformation agenda. The purpose of this paper is to discuss these gaps and offer directions for future research. Design/methodology/approach: Following a synthesis of literature on the UK's industry transformation agenda, the authors use the concepts of institutional logics, arrangements, complexity and strategic responses to suggest seven research questions that are at the nexus of policy-backed transformation and institutional theory. Findings: In this paper, the authors argue that increasing demands for the adoption and use of digital technologies, platforms, manufacturing approaches and other "industry-4.0"-related technologies will reconfigure existing logics and arrangements in the construction industry, creating a problem of institutional complexity for general contracting firms in particular. Originality/value: The questions are relevant for our understanding of the nature of institutional complexities, change, strategic firm responses, field-level dynamics and implications for the construction industry in relation to the transformation agenda. This paper is positioned to spur future research towards exploring the consequences of industry transformation through the lens of institutional theory.